Carbon Sequestration in the Green Open Spaces along Primary Road of Pontianak City, West Kalimantan, Indonesia - Hardiansyah, Gusti; Indrianingrum, Dewi Ratnasari; Anwari, M. Sofwan; Haryono, Zuhry; Diba, Farah; Ekamawanti, Hanna Artuti; Yani, Adi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Global climate change caused by greenhouse gas (GHG) emissions is currently a focus for various countries worldwide, including Indonesia. Carbon dioxide (CO2) is the main source of emissions, with a significant portion originating in urban areas. This is due to the high levels of air pollution from motor vehicles and rapid industrial growth. Urban green spaces are areas within cities that consist of non-built-up spaces filled with naturally grown or cultivated vegetation. These green spaces exist directly alongside the transportation infrastructure, which helps reduce air pollution, especially CO2, through the vegetation that makes up these areas. One type of urban green space is a green corridor, which forms elongated paths or areas. This study assessed the carbon sequestration of 17 primary road networks in Pontianak City using three allometric models. Plot positions for data collection were determined using purposive sampling, with each side accounting for 5% of the total zigzag plots. This research focused on vegetation at different growth stages, such as saplings, poles, and trees. The results were estimated at 256.86 tons ha-1 (Hardiansyah and Ridwan formula), 269.96 tons ha-1 (Chave formula), and 193 tons ha-1 (Brown formula).